Involvement of PI3-kinase and its association with c-Src in PTH-stimulated rat enterocytes - Gentili, Claudia Rosana (2002)
Phosphoinositide-3-kinase (PI3K) is a lipid kinase, which phosphorylates the D3 position of phosphoinositides, and is known to be activated by a host of protein tyrosine kinases. PI3K plays an important role in mitogenesis in several cell systems. However, whether parathyroid hormone (PTH) affects the activity and functional roles of PI3K in intestinal cells remain to be determined. The objective of this study was to identify and characterize the PI3K pathway, and its relation to other non-receptor tyrosine kinases in mediating PTH signal transduction in rat enterocytes. PTH dose- and time-dependently increased PI3K activity with a peak occurring at 2 min. The tyrosine kinase inhibitor genistein, c-Src inhibitor PP1 and two structurally different inhibitors of PI3K, LY294002 and wortmannin, suppressed PI3K activity dependent on PTH. Co-immunoprecipitation analysis showed a constitutive association between c-Src and PI3K, which was enhanced by PTH treatment, suggesting that the cytosolic tyrosine kinase forms an immunocomplex with PI3K probably via the N-SH2 domain of the p85α regulatory subunit. In response to PTH, tyrosine phosphorylation of p85α was enhanced, effect that was abolished by PP1, the inhibitor of c-Src kinase. PTH causes a rapid (0.5-5 min) phosphorylation of Akt/PKB, effect that was abrogated by PI3K inhibitors, indicating that in rat enterocytes, PI3K is an upstream mediator of Akt/PKB activation by PTH. We report here that PI3K is also required for PTH activation of the mitogen-activated protein kinases ERK1 and ERK2. Taken together, the present study demonstrate, for the first time, that PTH rapidly and transiently stimulates PI3K activity and its down effector Akt/PKB in rat enterocytes playing c-Src kinase a central role in PTH-dependent PI3K activation and that PI3K signaling pathway contributes to PTH-mediated MAPK activation. © 2002 Wiley-Liss, Inc.